FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI PADA BALITA - Gani, Kameriah; Rahmadani, Risna Ayu; Widhi, Anisa Sekar; Febsi, Yania; Utami, Kurniati Dwi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Stunting prevalence in Pekanbaru City 2021 is 11.4% to 16.8% in 2022. Nutritional problems in children will interfere with the process of child development, both mentally and physically, such as physiological disorders and body metabolism which can lead to death, reduce thinking ability, reduce human resources and work productivity and ultimately nutritional problems can lead to a decrease in the quality of the nation. The purpose of the study was to determine what is associated with nutritional status in toddlers in Pekanbaru City. This research design is cross sectional. The research time began in November 2021 at 5 Puskesmas Pekanbaru City. The study population amounted to 1200 people and sampling was 92 respondents using stratified random sampling technique. Data analysis used is univariate and bivariate. The results of the study with statistical tests showed a knowledge value of p value: 0.028, economic status p value 0.001, and parenting pattern p value 0.002. The recommendation of the results of this study is that respondents should have comprehensive knowledge about nutrition and provide better nutrition to toddlers so that the nutritional status of children on normal or good values.Keywords: Nutritional status, knowledge, economic status, parenting style